Groups, norms and endogenous membership - Raul V. Fabella (University of the Philippines, School of Economics (UPSE), 2016)
In Part I, we argue that Economics must outgrow the narrow confines of Neo-Classical Economics to embrace 'sociality' first championed by Herbert Simon in the mid-1950s and now by a growing number of economists under the banner of Social Economics. We contend here that Neo-Classical Economics is incomplete, rather than wrong. Firstly any alternative model must subsume the Neo-Classical model as a special case even as it embraces conceptual promontories from other social science disciplines, viz., groups, norms and sanctions. Secondly, it must be couched in a language familiar to the economics profession-maintain optimizing behavior and equilibrium analysis. In Part II, we construct a formal model where the agent is at once a private entity and a member of a social group; his utility is inclusive combining the agent's private utility over goods (the Neo-Classical utility) and the utility the he derives from being a member, viz., access to group's collective good. As a member, he commits to support the procurement of the group's collective good and submits to a system of norms and to the corresponding self-organized sanctions regime punishing violation of group norms. The agent solves a sequence of optimization problems: the first determines his optimal consumption basket given his budget constraint (net of group contribution), prices in the market location of the group; this gives his inclusive indirect utility; the second determines his optimal market hours by maximizing his indirect inclusive utility subject to time constraint and the market wage rate; this gives his doubly indirect inclusive utility; thirdly, he maximizes his inclusive doubly indirect utility with respect to the monetary contribution of the group given the sanctions for norm violation. The choice of social group follows from a rank order of groups by greatest inclusive utility an agent can attain in each competing social group. Finally, we show how the agent's relative weighting of his private and group commitment may wax and wane depending upon the stakes of the inter-group competition.
Keywords: D01; D11; 330; sociality; groups; norms; choice of groups; compliance with norms; inter-group competition